Educational administration : - Lunenburg, Frederick C. (Wadsworth, 2008)
Lunenburg (educational leadership, Sam Houston State University) and Ornstein (administrative and instructional leadership, St. John's University) have added new material on the latest national policies and trends in school law, school finance, and careers in school administration, in this fourth edition of a text exploring all facets of educational administration. Updated material on theory looks at school improvement and social justice, and there are new profiles of school superintendents and principals.